Voprosy social'noj lingvistiki. [Pri učast. V.M. Žirmunskogo, N.D. Andreeva, R.G. Piotrovskogo i dr. Pod red. A.V. Desnickoj, V.M. Žirmunskogo, L.S. Kovtuna i dr.] ("Nauka", 1969)
AN SSSR. Leningradskoe otdelenie Instituta jazykoznanija.